Bauran Pemasaran Tempe UD. Tiga Putra Arema di Kabupten Sumbawa Nusa Tenggara Barat - Wijayanti, Nila; Angkasa, Aries Zuhri; Nurwahidah, Siti; Wartiningsih, Alia; Fadhila, Mar (Musamus University, 2023)
Tempe is a traditional Indonesian food that is similar to that of the people of Sumbawa Regency. Trading business Tiga Putra Arema is one of the Tempe producers in Sumbawa Regency. The Tempe business requires an effort in marketing. The 4P marketing mix is a business strategy prioritized for product, price, location, and promotion. The purpose of this study is to describe the marketing mix of the trading business of Tiga Putra Arema Tempe in Sumbawa Regency. This research was conducted in May–July 2023. The number of samples in this research was 30 respondents. Data analysis uses descriptive analysis. The final results were obtained from the Likert scale and then entered into the weighted mean score formula. The most important aspect of marketing mix Tempe indicated that price was the component that had a high weighted mean score, namely 4.25 (very good), product with an average score of 4.21 (very good), location with an average score of 4.13 (good), and promotion with an average score of 3.83 (good).